IMPLEMENTATION OF POLICY NO. 46 OF 2023 ON THE PREVENTION AND HANDLING OF VIOLENCE IN KINDERGARTENS IN PIDIE REGENCY - Marlinda, Nila; Yanti, Hera; Rizki, Sari (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Cases of violence and bullying within educational settings in Indonesia have become a serious issue, with 2,355 recorded violations of child protection in the education sector as of August 2023. Bullying most frequently occurred at the elementary and junior high school levels (25% each), followed by senior high schools and vocational schools (18.75% each), Islamic junior high schools (6.25%), and Islamic boarding schools (6.25%). Specifically, Aceh Province has also reported a significant number of bullying and sexual violence cases, with 575 cases of sexual violence against women and children recorded by June 2023. In response to the widespread prevalence of harassment cases in Indonesia, particularly in Pidie District, the Ministry of Education issued Regulation No. 46 of 2023 concerning the Prevention and Handling of Violence in Educational Settings. This regulation aims to create a safe and effective learning environment, one of its key measures being the establishment of a Team for the Prevention and Handling of Violence (TPPK) in every educational institution. However, the implementation of this regulation still faces challenges, especially in Pidie District. Observations indicate that the formation of TPPK has not been optimal, particularly at the kindergarten to junior high school levels, whereas senior and vocational high schools—under provincial government authority—have demonstrated more efficient implementation. Although there have been previous studies discussing the prevention and handling of violence in educational environments—whether related to Regulation No. 46 of 2023 or efforts to prevent bullying through character education—these studies tend to focus on narrow scopes. Therefore, this study specifically examines “The Implementation of Regulation No. 46 of 2023 on the Prevention and Handling of Violence in Kindergartens in Pidie District.” This research is crucial for assessing the effectiveness of policy implementation on a broader scale and for emphasizing the importance of early prevention, considering that violent and bullying behavior is often part of a long-term pattern